2022
DOI: 10.2147/jir.s359887
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Extracellular Vesicles Mediated miRNAs in Osteoarthritis: Current Knowledge and Perspective

Abstract: Osteoarthritis (OA) is a whole joint disease characterized by synovitis, cartilage destruction, and subchondral bone sclerosis and cyst. Despite decades’ study, effective treatment is rare for this chronic disease. Extracellular vesicles (EVs), including exosomes, microvesicles, and apoptosis bodies, are nano-sized vesicles with a cargo containing biologically active agents, such as nucleic acids, lipids, and proteins. As a group of short non-coding RNAs, microRNAs (miRNAs) can be delivered by parental cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 133 publications
(176 reference statements)
0
6
0
Order By: Relevance
“…Additionally, ADSC‐Exos have been shown in an in vitro investigation to lessen inflammatory responses and oxidative stress in OA osteoblasts 241 . Tables 5 and 6 as well as Figure 12 display all recent publication highlighting the use of exosomes and EVs for the management of OA 242 …”
Section: Exosomes and Autoimmune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ADSC‐Exos have been shown in an in vitro investigation to lessen inflammatory responses and oxidative stress in OA osteoblasts 241 . Tables 5 and 6 as well as Figure 12 display all recent publication highlighting the use of exosomes and EVs for the management of OA 242 …”
Section: Exosomes and Autoimmune Disordersmentioning
confidence: 99%
“…Schematic diagram of potential factors that affect the management of EVs‐miRNAs, which might further affect its clinical application in human OA. Reprinted with permission from Shang et al 242 …”
Section: Exosomes and Autoimmune Disordersmentioning
confidence: 99%
“…In addition, small ncRNAs, embedded in ribonucleoproteins and lipoproteins, are found to be secreted into extracellular spaces [ 13 ]. An increasing number of studies have detected extracellular small ncRNAs in a variety of biological fluids, such as serum or plasma, and indicated that extracellular small ncRNA profiles in various body fluids could serve as novel biomarkers for different pathological conditions [ 14 , 15 , 16 , 17 ]. As one of the most abundant RNA species in circulation, extracellular small ncRNAs are actively involved in a variety of pathological and physiological processes.…”
Section: Ex-ncrnasmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are lipid bilayer structures secreted by living cells and are classified into either exosomes, microvesicles (MVs), or apoptotic bodies, based on the intracellular production mechanism and size ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , …”
Section: Introductionmentioning
confidence: 99%